2017
DOI: 10.1016/j.bbr.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neonatal amygdala or hippocampus lesions on adult social behavior

Abstract: The present report details the final phase of a longitudinal evaluation of the social behavior in a cohort of adult rhesus monkeys that received bilateral neurotoxic lesions of the amygdala or hippocampus, or sham operations at 2 weeks of age. Results were compared to previous studies in which adult animals received amygdala lesions and were tested in a similar fashion. Social testing with four novel interaction partners occurred when the animals were between 7 and 8 years of age. Experimental animals interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
(82 reference statements)
2
30
2
Order By: Relevance
“…Pharmacologically increasing amygdala activity results in decreased social interaction in monkeys 58 , which provides a potential mechanism to explain our results showing increased functional connectivity between the amygdala and prefrontal area 46, as well as the amygdala and caudate among ZIKV-infected infant RMs. In addition, previous studies of RMs with selective lesions of the amygdala or hippocampus during infancy report similar alterations in socioemotional behavior [59][60][61][62][63] , further supporting the notion that behavioral changes in the current study may be the result of structural and functional alterations found in these limbic regions after postnatal ZIKV infection. Overall, these findings indicate that ZIKV infection during this early and vulnerable period of rapid postnatal brain development can have a lasting impact on socioemotional behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Pharmacologically increasing amygdala activity results in decreased social interaction in monkeys 58 , which provides a potential mechanism to explain our results showing increased functional connectivity between the amygdala and prefrontal area 46, as well as the amygdala and caudate among ZIKV-infected infant RMs. In addition, previous studies of RMs with selective lesions of the amygdala or hippocampus during infancy report similar alterations in socioemotional behavior [59][60][61][62][63] , further supporting the notion that behavioral changes in the current study may be the result of structural and functional alterations found in these limbic regions after postnatal ZIKV infection. Overall, these findings indicate that ZIKV infection during this early and vulnerable period of rapid postnatal brain development can have a lasting impact on socioemotional behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Lesion placement has been confirmed at various time points using MRI and more recently by direct histological analysis (Bliss-Moreau, Moadab, Santistevan, & Amaral, in press). Edema associated with brain lesions was measured 10 days post-surgery, using T2-weighted magnetic resonance images.…”
Section: Methodsmentioning
confidence: 99%
“…We used the Observer 5.0 software package (Noldus, Wageningen, NL) and our standard behavioral ethogram (Bliss-Moreau et al 2017) (Supplementary Table 1), in order to analyze each monkey’s behavior during the individual exploration session. Quantitative analyses of exploratory behavior demonstrated that both groups of animals were motivated to explore the novel environment.…”
Section: Resultsmentioning
confidence: 99%